Orígenes del Fútbol en Barcelona (1892-1903). | Origins of Fooball in Barcelona (1892-1903). - Xavier Torrebadella Flix (Ramón Cantó Alcaraz, 2012)
This article shows some unpublished data that seek to clarify the origins of football in Spain and particularly in Barcelona. Apart from the influence of the English colony in the dissemination of football, the background of school sport is described and evaluated. It is provided data about football in Barcelona which reveal that before the constitution of the Football Club Barcelona, often considered the first team of the city, there were ten associations that practiced this sport. It emphasizes the importance of the British colony, gyms and sports clubs of Barcelona from 1892 to 1903, to generate the enabling environment that made ​​the modern sport of football triumph, stimulating in turn the context Regenerationism and the emergence of associations sports from the early twentieth century. The research method has focused on historical analysis techniques, with the treatment of the original documentary sources and complemented with historicist indirect sources. Resumen En este artículo se presentan algunos datos inéditos que pretenden esclarecer los orígenes del fútbol en España y más concretamente en Barcelona. Aparte de la influencia que ejerce la colonia inglesa en la divulgación del fútbol, se describen y se valoran los antecedentes del deporte escolar. Sobre el fútbol en Barcelona se aportan datos que revelan que antes de la constitución del Fútbol Club Barcelona, considerado frecuentemente como el primer equipo de fútbol de la ciudad, existieron una decena de asociaciones que practicaron este deporte. Se acentúa la importancia que tuvo la colonia inglesa, los gimnasios y las sociedades deportivas de Barcelona entre 1892 y 1903, para generar el ambiente favorable que hizo que el fútbol triunfase como deporte moderno, estimulando a su vez el contexto regeneracionista y la emergencia del asociacionismo deportivo de principios del siglo XX. El método de investigación se ha centrado en técnicas de análisis histórico en torno al tratamiento de las fuentes documentales originales y el complemento de otras fuentes historicistas indirectas.